PENGARUH LATIHAN MEMUKUL BOLA GANTUNG TERHADAP HASIL SMASH PADA PERMAINAN BOLA VOLI - Manullang, Jujur Gunawan; Ngatimin (Indonesian Journal of Physical Education and Sport Science, 2023)
Study purpose. This study aims to determine whether there is an influence between the practice of hitting the ball on the results of volleyball smashes in extracurricular male students at SMA Negeri 1 Belitang 1. Materials and Methods. In this study the method used was an experiment with the design of One Group Pre test Post test, namely statistics to determine the influence between two symptoms, the data collection technique used was by test. Smash punch test to measure the results of a smash punch in a volleyball game. The population in this study was male students who participated in volleyball training activities at SMA Negeri 1 Belitang 1. The sample consisted of 14 male students of SMA Negeri 1 Belitang 1. Results. The magnitude of the influence between the practice of hitting the ball on the results of the smash punch was that it could be seen by the hypothesis using the t test obtained a t count of 1.951 and a t table price of 1.761. So t count > t table, thus Ha was accepted and Ho was rejected, which means that there is a significant effect of the practice of hitting the ball on the results of volleyball smashes in extracurricular male students at SMA Negeri 1 Belitang 1. Conclusions. The conclusions of this study indicate that there is a significant effect of hitting the ball practice on smash results in volleyball extracurricular students at SMA Negeri 1 Belitang 1.